Recrystallization and damage of ice in winter sports - Seymour-Pierce, A.; Lishman, B.; Sammonds, P. (Philosophical transactions of the Royal Society A - Mathematical, physical and engineering sciences,, 2017)
Ice samples, after sliding against a steel runner, show evidence of recrystallization and microcracking under the runner, as well as macroscopic cracking throughout the ice. The experiments that produced these ice samples are designed to be analogous to sliding in the winter sport of skeleton. Changes in the ice fabric are shown using thick and thin sections under both diffuse and polarized light. Ice drag is estimated as 40-50% of total energy dissipation in a skeleton run. The experimental results are compared with visual inspections of skeleton tracks, and to similar behaviour in rocks during sliding on earthquake faults. The results presented may be useful to athletes and designers of winter sports equipment.